Correlation between Leisure Activity Time and Life Satisfaction: Based on KOSTAT Time Use Survey Data - Yu-Jin Cha (Occupational Therapy International)
Rationale. This study aims to investigate the correlation between the available leisure activity time and life satisfaction of the healthy elderly and the factors affecting them. Method. For the analysis, data from the 2014 Time Use Survey (2014TUS) published by Statistics Korea (KOSTAT) was used. This study classified the detailed activities of 9228 subjects, based on the data in 2014TUS, and analyzed the differences in time use for occupation domains by age group. Results. It was found that a greater amount time used for outdoor leisure activities yielded a higher life satisfaction value. Differences were found in time use by occupation domains between younger and older groups. These showed higher life satisfaction for those with spouses, regular full-time jobs, higher education, and better health. Conclusion. Based on these results, in order to improve the quality of life (QoL) for older adults, it is necessary to develop various leisure programs that require dynamic physical activities and to prepare alternative policies at the national level to promote participation in leisure activities by older adults. This study will provide occupational therapists (OTs) with data they can use to help older adults who have difficulty in time usage through time management intervention to improve their life satisfaction and QoL.